Transformative therapies for rare CFTR missense alleles. (June 2017) - Oliver, Kathryn E; Han, Sangwoo T; Sorscher, Eric J; Cutting, Garry R
Highlights: CFTR missense alleles exhibit diverse mechanisms of dysfunction. Compounds targeting specific classes of CFTR defects have been variably successful. Methods and models utilized for studying CFTR variants are continually improving. Characterizing each CFTR variant will facilitate approaches to precision medicine. Genetic tools under development may lead to future treatments for all forms of CF. Abstract : With over 1900 variants reported in the cystic fibrosis transmembrane conductance regulator (CFTR), enhanced understanding of cystic fibrosis (CF) genotype–phenotype correlation represents an important and expanding area of research. The potentiator Ivacaftor has proven an effective treatment for a subset of individuals carrying missense variants, particularly those that impact CFTR gating. Therapeutic efforts have recently focused on correcting the basic defect resulting from the common F508del variant, as well as many less frequent missense alleles. Modest enhancement of F508del-CFTR function has been achieved by combining Ivacaftor with Lumacaftor, a compound that aids maturational processing of misfolded CFTR. Continued development of in silico and in vitro models will facilitate CFTR variant characterization and drug testing, thereby elucidating heterogeneity in the molecular pathogenesis, phenotype, and modulator responsiveness of CF.